PENERAPAN METODE FORWARD CHAINING PADA APLIKASI TES KEPRIBADIAN BERDASARKAN DISC UNTUK PENINGKATAN KARIR KARYAWAN DI PT. INTEGRIYA DEKORINDO BERBASIS ANDROID - Galih Haryanto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Android applications are being used by the general public and are beneficial in many different fields, particularly in the data industry. Data that is obtained from previously developed applications, such as bidding applications, web-based applications, and other applications, may change over time depending on the Android application in question. Android applications are also used to obtain records of human information, including human information directly. Despite this, a significant portion of the population still engages in TES, which is typically conducted in a physical manner. Due to this, an Android app was created in the study to obtain data on a person's character so that the subject could easily obtain statistics on their character. Tes character is also classified into several types, such as those that are revealed by the technique for human character analysis that is being used. In this review, the technique for human character pemisahan that will be used is called Humanity is classified according to the DISC principles of Dominance, Influence, Stability, and/or Compliment. The application in question makes use of the forward chaining method to gather information from the tester's sifat, and it will subsequently be used to convey the application's conclusion in the end. This application is reviewed by 20 people who fill it out honestly, and it is then reviewed several times for consistency in the number of topics covered. From the application's development came more kecocokan with increasingly clear instructions that the system gives to users.